Automated implantable cardioverter defibrillator lead infection in a patient with previous superior vena cava thrombosis. (4th November 2015) - Connelly, Tara; Siddiqui, Sadiq; Kolcow, Walenty; Veerasingam, Dave
Abstract : We present a case of a 44-year-old woman who presented with cough, pleuritic chest pain and fever leading to a diagnosis of pneumonia±pulmonary embolism. She had a history of familial hypertrophic obstructive cardiomyopathy (HOCM), for which an automated implantable cardioverter defibrillator (AICD) had been implanted, and a subsequent superior vena cava (SVC) thrombus, for which she was anticoagulated with warfarin. On admission, blood cultures grew a coagulase-negative Staphylococcus . CT pulmonary angiogram and transoesophageal echocardiography (TOE) were performed and revealed large vegetations adherent to the AICD leads with complete occlusion of the SVC. The infected leads were the source of sepsis. Open surgery was planned. For cardiopulmonary bypass, the venous cannula was inserted in the inferior vena cava (IVC) and a completely bloodless field was obtained in the right atrium allowing for the extraction of the AICD leads completely, along with the adherent vegetations from within.